Retrospective study on rib fractures: smoking and alcohol matter for mortality and complications. Issue 1 (15th June 2021) - Gongola, AlleaBelle; Bradshaw, Jace C; Jin, Jing; Jensen, Hanna K; Bhavaraju, Avi; Margolick, Joseph; Sexton, Kevin W; Robertson, Ronald; Kalkwarf, Kyle J
Abstract : Background: Rib fractures and substance use are both common in trauma patients, but there is little data on how smoking and alcohol use may be associated with outcomes in these patients. We assessed the association between smoking or alcohol use disorder (AUD) and outcomes in patients with rib fractures. Methods: We used institutional databases to conduct a retrospective review of patients with rib fractures at the only American College of Surgeons-verified adult level 1 trauma center in a rural state between 2015 and 2019. The key exposure variables were smoking and AUD. The key outcome variables were mortality and pulmonary complications (pneumonia, adult respiratory distress syndrome, and pneumothorax). We used multivariable regression for analysis and directed acyclic graphs to identify variables for adjustment. Results: We identified 1880 eligible patients with rib fractures, including 693 (37%) who were smokers and 204 (11%) who had AUD. Compared with non-smokers, smokers were younger, more often male, and had lower mortality rates. Regression showed that smokers had a lower likelihood of mortality (OR 0.48; 95% CI 0.27 to 0.87; p=014). Likelihood of pneumonia, ARDS, and pneumothorax was not different between smokers and non-smokers. Compared with patients without AUD, patients with AUD were older, more often male, and had higher likelihood of pneumonia and lower likelihood of pneumothorax. Regression showed that patients with AUD had higher likelihood of pneumonia (OR 1.82; 95% CI 1.24 to 2.68; p=0.002) and lower likelihood of pneumothorax (OR 0.51; 95% CI 0.33 to 0.75; p=0.002). Discussion: In trauma patients with rib fractures treated at a level 1 trauma center over 5 years, smoking was associated with decreased risk of mortality. These findings have implications for risk stratification and clinical decision-making for patients with rib fractures. Level of evidence: III